2021
DOI: 10.1021/acs.joc.1c01814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dihydroquinolinone Derivatives via the Cascade Reaction of o-Silylaryl Triflates with Pyrazolidinones

Abstract: Presented herein is a novel synthesis of dihydroquinolinone derivatives through an unprecedented cascade reaction of o-silylaryl triflates with pyrazolidinones. Mechanistically, the formation of the title products is believed to involve a cascade procedure including in situ formation of aryne and its addition with pyrazolidinone followed by N−N bond cleavage and intramolecular C−C bond formation/annulation. Compared with literature methods for the synthesis of dihydroquinolinones, this protocol has advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Encouraged by this reaction outcome, we further optimized the reaction by adding TBAB : oxalic acid (1 : 1 (100 : 100 mg)) DES to step 2, leading to an increased product yield of 52% (Table 1, entry 12). Based on this result, the reactions were further explored using TBAB-based DESs such as TBAB : tartaric acid (1 : 1), TBAB : citric acid (1 : 1), TBAB : ethylene glycol (1 : 1), TBAB : succinic acid (1 : 1), TBAB : sucrose (1 : 1), TBAB : glycerol (1 : 1) and TBAB : PTSA (1 : 1) (Table 1, entries [13][14][15][16][17][18][19]. From these trials, we have observed that a 58% yield of product 4A was achieved using the TBAB : PTSA (1 : 1) DES ( 1, entries 23-27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Encouraged by this reaction outcome, we further optimized the reaction by adding TBAB : oxalic acid (1 : 1 (100 : 100 mg)) DES to step 2, leading to an increased product yield of 52% (Table 1, entry 12). Based on this result, the reactions were further explored using TBAB-based DESs such as TBAB : tartaric acid (1 : 1), TBAB : citric acid (1 : 1), TBAB : ethylene glycol (1 : 1), TBAB : succinic acid (1 : 1), TBAB : sucrose (1 : 1), TBAB : glycerol (1 : 1) and TBAB : PTSA (1 : 1) (Table 1, entries [13][14][15][16][17][18][19]. From these trials, we have observed that a 58% yield of product 4A was achieved using the TBAB : PTSA (1 : 1) DES ( 1, entries 23-27).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, here Cu( ii ) and TEMPO facilitate the dehydrogenation of alcohol 3 , to form aldehyde 3′ . 18 Then, aldehyde 3′ undergoes a nucleophilic addition to the enamine intermediate C′ , followed by condensation, leading to the formation of intermediate 4 . Furthermore, intermediate 4 undergoes a Knoevenagel condensation 43 with another mole of aldehyde ( 3′ ) to form the final product 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of this skeleton compound has stimulated activities of the synthesis community to develop new transformation strategies that can obtain DHQO compounds. In the past decades, some new synthetic methods have been continuously developed, such as the Pd-catalyzed Heck reduction-cyclization reaction [7], Pd-catalyzed cyclopropane ring expansion [8], Mn-mediated intramolecular cyclization [9], Rh-mediated Michaeladdition (1,4-additions) of the boronic acid to enone [10], Ru catalyzed cyclization of 1,4,2-dioxazol-5-ones [11], photoredox strategy from anilines, oxalyl chloride and electrondeficient alkenes [12], and so on [13][14][15][16][17][18][19]. Among these, using α,β-unsaturated N-arylamides as the key substrates via different cyclization reactions has been shown as a fast, simple, and atom-economic strategy.…”
Section: Introductionmentioning
confidence: 99%